Inventory and update on argasid ticks and associated pathogens in Algeria. (May 2018) - Lafri, I.; Benredjem, W.; Neffah-Baaziz, F.; Lalout, R.; Abdelouahed, K.; Gassen, B.; Bakhouch, S.; Chergui, M.; Karakellah, M.; Adjmi-Hamoudi, H.; Bitam, I.
Abstract: Argasid ticks include vectors of relapsing fevers caused by Borrelia spp. in humans, and they can transmit arboviruses and other bacterial pathogens. Knowledge about soft ticks ( Ixodida: Argasidae ) in Algeria is incomplete, and distribution data need to be updated. Here we report a series of entomologic investigations that we conducted in five different areas in Algeria between 2012 and 2015. Ticks were identified by entomologic keys and molecular tools (16S rRNA gene). Six distinct species belonging to two genera were identified, including Ornithodoros capensis s.s., Ornithodoros rupestris, Ornithodoros occidentalis, Ornithodoros erraticus, Ornithodoros sonrai and Argas persicus. The present study highlights the distribution of soft ticks, the establishment of an update inventory with nine species and associated pathogens detected in argasid ticks in Algeria.